Design and development of hybrid solar dryer for flowers - PACHPINDE, PADMAPANI; SHARMA, P K; MANI, INDRA; PARRAY, ROUF A; NAMITA, NAMITA (The Indian Journal of Agricultural Sciences, 2019)
A hybrid solar dryer was developed consisting of three shelves of 0.55 m2 area each in the drying chamber. This dryer works on the principal of solar thermal and solar photovoltaic system. The performance evaluation was done with rose and marigold flowers. It was found that both flowers when dried at 45Â°C were significantly (P <0.05) better in terms of retention of anthocyanin and carotenoid content, shape, texture, brittleness, intactness, colour and per cent reduction in diameter. Moisture content (w.b) reduction from 90â€“14%, total drying time (h), reduction in diameter (%), overall drying rate (%/h) and anthocyanin content (mg/g) for solar dried sample was 31.66, 7.43, 2.32 and 2.49 respectively, whereas for control (sun dried) it was found to be 53.66, 17.85, 1.38 and 1.21 respectively. The time of drying was lesser by 65% and 70% for rose and marigold flowers when dried in solar dyer.The sensory analysis showed that solar dried samples were superior in terms of shape, colour, texture, brittleness and intactness as compared to control. Thus the overall acceptability of flowers dried using the developed dryer was better.